Electroacupuncture for pain relief in labour inhibits spinal p38 MAPK-mediated prostaglandin E2 release and uterine prostaglandin E2 receptor expression in rats. Issue 2 (April 2019) - Jiang, Gui-Xiu; Jiang, Qiu-Yan; Mo, Hai-Xia; Li, Li; Wang, Meng-Ying
Background: p38 mitogen-activated protein kinase (p38 MAPK) activation involves the release of prostaglandin E2 (PGE2) and hyperalgesia. We have previously reported that electroacupuncture (EA) relieves labour pain, but the potential mechanisms remain unclear. Objective: To observe the effects of EA on labour pain intensity, serum PGE2 levels and the p38 MAPK signalling pathway in rats during labour. Methods: Female rats copulated with male rats to induce pregnancy, and then received castor oil to trigger labour. During labour, rats remained untreated (Control group, n=30) or were treated with remifentanil (n=30) or EA at Jiaji (n=30) or SP6+LI4 (n=30), respectively. The warm water tail-flick test was used to assess labour pain. Serum PGE2 levels were measured by ELISA. Protein expression of prostaglandin E2 receptor (PGER2), p38 MAPK and phospholipase A2 (PLA2) were analysed by Western blotting, and mRNA levels were measured by real-time PCR. Results: EA treatment at Jiaji or SP6+LI4 significantly relieved labour pain, decreased serum PGE2 levels and inhibited protein and gene expression of PGER2 in the myometrium. Moreover, EA reduced protein expression of PLA2 and p38 MAPK, and inhibited phosphorylation of p38 MAPK in the lumbar spinal cord but not in the cerebral grey matter. Additionally, EA markedly decreased mRNA levels of p38 MAPK in the lumbar spinal cord and significantly reduced PLA2-IV mRNA levels in both the lumbar spinal cord and cerebral grey matter. Conclusions: This study indicates that EA relieves labour pain through, at least in part, inhibition of spinal p38 MAPK-mediated PGE2 release and uterine PGER2 expression in rats.